Measuring Maturity Level On The Process Of Developing An Online Presence System With CMMI Framework - I Gede Sudiantara (International Journal of Engineering and Emerging Technology, 2021)
The development of information technology has spurred new ways of life that meet people's electronic needs, such as e-commerce, e-government, e-education, and so on. IT involvement in an institution or organization causes system changes that have an impact on changes in the way of performance [1]. Good use of technology is important for local governments [2]. In addition to facilitating the reporting process, information systems can support the main tasks and functions of government. The online presence system is one of the supporting tools in government to support the implementation of e-government. To support the quality of the system and increase the trust of interested parties, it is necessary to conduct an audit of the online presence system development process. Measuring the level of maturity of the online presence system development process using the CMMI framework. The percentage of maturity level in the presence system development process is 73.33 at level 2. Each process area of ??CMMI can be achieved through a questionnaire that has been distributed to the team involved in the online presence system development process.